Effect of the IrOx Conductivity on the Anode Electrode/Porous Transport Layer Interfacial Resistance in PEM Water Electrolyzers. Issue 8 (27th August 2021) - Bernt, M.; Schramm, C.; Schröter, J.; Gebauer, C.; Byrknes, J.; Eickes, C.; Gasteiger, H. A.
Abstract : In this study, a commercial IrO2 /TiO2 catalyst (75 wt% Ir, named "Benchmark") for the oxygen evolution reaction (OER) is compared to a newly developed IrO(OH)x /TiO2 catalyst (45 wt% Ir, named "P2X"). Due to its lower Ir packing density and higher OER activity vs the Benchmark catalyst (440 vs 12 A gIr −1 at 1.43 ViR-free ), the P2X catalyst shows an improved PEM (proton exchange membrane) water electrolyzer performance at ≈9 times reduced Ir loading, however, only if a platinum-coated porous transport layer (PTL) at the anode is used. While the performance of membrane electrode assemblies (MEAs) with the Benchmark catalyst is unaffected when using an untreated titanium PTL, MEAs with the P2X catalyst perform poorly, which can be attributed to a contact resistance at the anode/PTL interface due to the low electrical conductivity of the P2X catalyst (0.7 S cm −1 ) vs the Benchmark catalyst (416 S cm −1 ) and the passivation of the Ti-PTL. A heat treatment procedure is used to transform the amorphous IrO(OH)x of the P2X catalyst into crystalline IrOx and, hence, increases its electrical conductivity. The optimum temperature for heat treatment to maximize electrical conductivity, OER activity and MEA performance will be evaluated.